2022
DOI: 10.1097/jhm-d-21-00208
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Healthcare Organization Actions and Policies Related to COVID-19 on Perceived Organizational Support Among U.S. Internists: A National Study

Abstract: may promote healthcare worker mental health, but organizational factors that foster POS during the COVID-19 pandemic are unknown. The goals of this study were to identify actions and policies regarding COVID-19 that healthcare organizations can implement to promote POS and to evaluate the impact of POS on physicians' mental health, burnout, and intention to leave patient care. Methods:We conducted a cross-sectional national survey with an online panel of internal medicine physicians from the American College o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…The healthcare team experienced signi cant stress and uncertainty, referred to as working in a pressure cooker, due to the COVID-19 pandemic. This is consistent with previous research that has shown that the unprecedented nature of the pandemic led to challenging working conditions, limited resources, lack of information, and concerns about infecting loved ones (32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44). The collective global impact of COVID-19 on healthcare systems is likely a contributing factor to these stressors (45)(46)(47)(48).…”
Section: Altruistic Behaviorssupporting
confidence: 88%
“…The healthcare team experienced signi cant stress and uncertainty, referred to as working in a pressure cooker, due to the COVID-19 pandemic. This is consistent with previous research that has shown that the unprecedented nature of the pandemic led to challenging working conditions, limited resources, lack of information, and concerns about infecting loved ones (32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44). The collective global impact of COVID-19 on healthcare systems is likely a contributing factor to these stressors (45)(46)(47)(48).…”
Section: Altruistic Behaviorssupporting
confidence: 88%
“…1,2 In September 2021, 76% of US healthcare workers reported burnout, compared with 54% in 2019. 3 Drivers of increased stress and burnout among physicians during the pandemic include individual-level factors like fear of exposure and transmission 4,5 and social isolation, 5,6 and organizational factors like inadequate personal protective equipment 7,8 and poor leadership. 7,9 Health inequities are an additional yet underrecognized source of physicians' occupational stress.…”
Section: Introductionmentioning
confidence: 99%
“…3 Drivers of increased stress and burnout among physicians during the pandemic include individual-level factors like fear of exposure and transmission 4,5 and social isolation, 5,6 and organizational factors like inadequate personal protective equipment 7,8 and poor leadership. 7,9 Health inequities are an additional yet underrecognized source of physicians' occupational stress. Wide-ranging racial-ethnic and socioeconomic health disparities prior to the onset of the COVID-19 pandemic are well established in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 The pandemic also accelerated mounting awareness of the role of organizational factors in shaping clinicians' work-related well-being. [27][28][29][30][31][32][33][34] Perspectives from occupational health and safety sciences have been instrumental to expanding the individualistic lens on clinician burnout and drawing attention to the work environment as a determinant of health and safety outcomes for the healthcare workforce. 1 Adverse work environments have been linked to poor mental health outcomes, 35 as has poor work-related social support.…”
Section: Introductionmentioning
confidence: 99%